Elevation heterogeneity and the spread of white-nose syndrome in bats - Read, Catherine E., author; Shipman, Patrick, advisor; Dangelmayr, Gerhard, committee member; Tulanowski, Elizabeth, committee member (Colorado State University. Libraries, 2018)
White-nose syndrome (WNS) has been decimating bat populations throughout North America since its discovery in New York during the winter of 2006-2007. The fungus responsible for the disease, Pseudogymnoascus destructans, has since been confirmed as present in Washington, over 3,700 km from the epicenter. In 2012, a stochastic discrete-time dynamical system for WNS spread was developed on a spatially structured network and used to predict the spread of this wildlife epidemic. The model uses a variable for distance and two environmental variables (cave density and winter duration) to generate spread probabilities between counties of the contiguous United States. However, predictions from the 2012 model missed several recently infected counties due to the use of a cave density variable. Major cave formations are both less frequent and poorly documented in the western U.S. Furthermore, cave density may not serve as an accurate proxy for bat hibernacula across the country considering the use of crevice and cavity roosts in rock substrates west of the Great Plains. A Terrain Ruggedness Index (TRI) can thus be calculated from elevation data and used in place of cave density to quantify elevation heterogeneity and represent crevice-dwelling bat populations. Incorporating TRI into the network spread model would generate more accurate WNS presence predictions and aid in more effective management efforts to contain the spread of this deadly bat disease.
Keywords: biomath; network; white-nose syndrome; epidemiology; bats; statistics